- - دکتر ساسان مهرانی; دکرت کاوه مهرانی; غلامرضا کرمی (بررسی‌های حسابداری و حسابرسی, 2004)
The potentinal role of predictive value of certain information in predicting stock returns have been the main issue that motivated researchers the make studies in order the find out about variables having significant relation to stock returns. These kind .of information content variables could be classified into two categories, financial and nonfinancial. The results of most type of these studies made by different researchers show that both financial and nonfinamcial information have significant effects on stock retrns. This paper also examines the relationships of stock returns and of both financial and nonfinancial measures. In this study six financial and nonfinancial variables have been selected tp examine their relationship with stock returns. In a cross-sectinal study we seleted all of the companies listed in Tehran stock Exchange during a two years period of 1381 and 1382 as our samples. We made use of mean return, regression and correlation of the variables the stock returns in order the test our hypotheses. The results of our study, as well as previous researches’ results, show that there is significant relationship between financial and nonfinancial variables and of stock returens. The results also show that the winner firms have more returns than that of loser ones.